Application of temperature simulation for seepage inspection in earth-fill dams - Somayeh Yousefi (Građevinar, 2013)
The earth-fill dam leakage is studied in this paper by applying the seepage flow and thermal simulation. The mass balance and convection-diffusion equations are discretized based on the finite element method to solve the phenomena in saturated and unsaturated zones. The Shamil embankment dam is used for verification of the proposed model. Different conductivity cases are analyzed and compared against measured data. Results show that investigation of temperature variations can magnify the effect of leakage more clearly than the inspection of seepage piezometric levels.